2011
DOI: 10.1038/nutd.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

Serum adiponectin level is not only decreased in metabolic syndrome but also in borderline metabolic abnormalities

Abstract: Objective:Along with the increasing prevalence of obesity and related diseases, particularly atherosclerotic diseases, metabolic syndrome (MetS) is now a common and major public health issue in many countries around the world. Adiponectin, a protein secreted by the adipose tissue, has become recognized as a key player in the development of MetS. These days, not only MetS but also borderline metabolic/physiological abnormalities, such as impaired fasting glucose, high normal blood pressure and high normal plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Characteristics of the study population are shown in Table 1 . Young obese subjects showed a borderline increase of SBP, DBP and MAP 25 . Additionally, obese subjects presented borderline risk factors for metabolic syndrome, including TC, LDLc, HDLc and TG 26 .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Characteristics of the study population are shown in Table 1 . Young obese subjects showed a borderline increase of SBP, DBP and MAP 25 . Additionally, obese subjects presented borderline risk factors for metabolic syndrome, including TC, LDLc, HDLc and TG 26 .…”
Section: Resultsmentioning
confidence: 84%
“…Metabolic syndrome was defined according to the International Diabetes Federation (IDF) criteria, to which central obesity (defined by WC) and ethnicity is an essential component for diagnosis of the syndrome and required the presence of two of the following elements: fasting plasma glucose (FPG) ≥ 100 mg/dL, systolic blood pressure (SBP) ≥ 130 mm Hg and diastolic blood pressure (DBP) ≥ 85 mm Hg, or on antihypertensive medication, TG ≥ 150 mg/dL or on treatment, HDLc < 40 mg/dL in men and < 50 mg/dL in women, or on treatment 21 . Additionally, borderline metabolic abnormalities for fasting glucose and high normal blood pressure (BP), as described by Baden et al 25 . Moreover, borderline lipid profile for metabolic syndrome factor, among these, TC, LDLc, HDLc and TG are described elsewhere 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Serum leptin has also been identified as an independent predictor of metabolic syndrome in men [ 46 ]. In contrast to leptin, adiponectin, an adipocyte-derived collagen-like protein, has been generally reported as a protective factor with an anti-inflammatory and anti-atherogenic properties [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has anti‐diabetic, anti‐hypertensive, anti‐inflammatory and anti‐arteriosclerotic properties . Hypoadiponectinemia is associated with an increased risk of type 2 diabetes, hypertension, dyslipidaemia, hyperuricemia, borderline metabolic abnormalities or arteriosclerotic disease . Hypoadiponectinemia is predominantly caused by obesity, especially visceral fat accumulation, and this phenomenon is the main molecular basis of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%